2001
DOI: 10.1001/archpsyc.58.6.529
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Estradiol for the Treatment of Depressive Disorders in Perimenopausal Women

Abstract: Transdermal estradiol replacement is an effective treatment of depression for perimenopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
125
0
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 604 publications
(134 citation statements)
references
References 39 publications
6
125
0
3
Order By: Relevance
“…There are numerous studies that have demonstrated the beneficial effects of oestrogen on mood in midlife women (52)(53)(54)(55). The Revised Global Consensus Statement on Menopausal Hormone Therapy (56) states that "MHT (menopausal hormone therapy) may be beneficial in improving mood in early postmenopausal women with depressive and/or anxiety symptoms.…”
Section: Treatmentmentioning
confidence: 99%
“…There are numerous studies that have demonstrated the beneficial effects of oestrogen on mood in midlife women (52)(53)(54)(55). The Revised Global Consensus Statement on Menopausal Hormone Therapy (56) states that "MHT (menopausal hormone therapy) may be beneficial in improving mood in early postmenopausal women with depressive and/or anxiety symptoms.…”
Section: Treatmentmentioning
confidence: 99%
“…Clinical studies indicate that E 2 may play a role in emotional behaviors [37,38,39,40,41,42]. We have demonstrated an ameliorative effect of E 2 in the forced swim test, a test for the efficacy of antidepressants [43].…”
Section: Introductionmentioning
confidence: 99%
“…The question is especially relevant given the existing mixed results with various antidepressants [1, 2], the possibility of using other antidepressant classes, such as dual action drugs [3, 4], and the potential role of hormonal therapies (e.g. estradiol) for the treatment of menopause-related depressive symptoms [5, 6]. …”
Section: Introductionmentioning
confidence: 99%